Anorexia nervosa stories : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts in Psychology at Massey University - Gibson, Marion (Massey University, 2005)
The wind, the seas, the storms unpredictability their nature howling, raging, destroying some soul structure hopelessly enveloped within an unknown grip a grip that tenses, strangles. (Diary extract, 1972) These words take me back 35 years ago to my lived experience of anorexia nervosa. It is this history that enabled me to question the relational narratives of anorexia - my own history and that of the women who participated in this research. This thesis is a study of the way women, who were once diagnosed as 'anorexic' story their lives. I wanted to find out what relationships and what cultural knowledges constituted their stories. I believe 'anorexic' stories are the starting point for understanding the meaning given to experiences of anorexia because it is the stories we live by which enable us to make sense of our lives. My study of these stories and their cultural knowledges has been informed by social constructionist and post-structuralist theories. These theories have enabled me to understand that the meanings we ascribe to our identities are mediated through power relations embedded in cultural discourses. Using Brown & Gilligan's (1992) voice-centered relational method for doing psychological research I have listened to three women's stories to understand how meaning was inscribed on their experiences of anorexia nervosa. My analysis of the women's stories focussed on the relational actions and events they experienced whilst growing up. I found it was the dominant relationships the women encountered which gave meaning to their lives and spoke to them of their thin identities. These were very thin identities, framed by our dominant cultural knowledges, and which, for women in our society specify a highly individual and gender specific way of being in the world. The possibilities for re-authoring our thin anorexia stories are also discussed.
Keywords: Anorexia nervosa patients; Meaning; Identity